A rapid CAE-based design method for modular hybrid truss structures - Walbrun, Simon; Witzgall, Christian; Wartzack, Sandro (Design Science, 2019)
The development of hybrid trusses made of carbon-fiber-reinforced plastic struts and aluminum knots is currently not standardized, and there is no overall method for the design, although it has been proven that mass reduction is feasible. This paper introduces a new method for computer-aided engineering based design of hybrid trusses using carbon-fiber-reinforced plastic struts and metal nodes based on a modular system. The method includes all design steps from topology optimization to computer-aided design model generation and offers support to the engineer. The method is discussed in theory. A case study is done with a beam-shaped truss. It shows that if the bisection optimization method is combined with further constraints, it is suitable for selecting the optimum struts from a modular system for the truss. The developed approach is a suitable method for designing hybrid trusses. The basis of the method has been developed and will be further detailed and extended.
CRIS-Team WoS Importer:2019-12-17

Baukastensystem für CFK-Fachwerkstrukturen – Diskrete Optimierung der Strebenquerschnitte - Walbrun, Simon; Wartzack, Sandro (Design for X - Beiträge zum 30. DfX-Symposium, 2019)
Fiber-reinforced plastics have a high potential for lightweight structures due to their high specific strength and stiffness. A modular system enables a reduction of the manufacturing costs for trusses by standardizing the components. The subdivision of the truss struts into groups and the selection of the profiles for the strut groups can be done by optimization with a genetic algorithm and the initial population generation by the bisection method. The proposed method reduces the number of necessary iterations and improves the optimum in comparison to the previous descriptions
Keywords: Genetic algorithms; Initial population; Optimization; Self-adaptive member grouping